الضوابط الشرعية لتحول البنك الزراعي الماليزي إلى مصرف إسلامي : دراسة تحليلية تقويمية - بوصيري، سعيد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Islamic bank is considered one of the fastest growing economic and financial institutions today, one of the factors contributing to this growth is the introduction of conversion methods and mechanism whereby conventional banks can convert their operation, products and services to Islamic. This however has call for continuous demand for the Shariah framework for converting a conventional bank into an Islamic bank. This study is therefore aimed to investigate into the existing Shariah standards for converting conventional bank into an Islamic bank with special focus on the conversion procedure of Agrobank Malaysia Berhad in disposing bank interest from deposit and loans, in order to measure the extent of the application of these standard and the level of compliance of the bank in observing the Shariah standards. The researcher has use the descriptive methodology in explaining the basic terminologies in the study and field study was conducted with the head of Shariah Committee for Agrobank on the conversion procedure of the bank and how the bank dispose off its accrued bank interest on bank deposits from customers and loans before the period of conversion. Agrobank as an Islamic bank that has developed it own Shariah framework among other criteria by consultation on necessary recommendations from Central Bank of Malaysia and AAOIFI. The study shows that Agrobank was able to fulfil it conversion obligation as an Islamic bank in Malaysia with certains challenges in disposing off its accrued bank interest from deposits and loans, and major challenge in creating awareness to the customers on the purpose and benefits of conversion.